5x+8888+x*(x-65)=1

Simple and best practice solution for 5x+8888+x*(x-65)=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+8888+x*(x-65)=1 equation:


Simplifying
5x + 8888 + x(x + -65) = 1

Reorder the terms:
5x + 8888 + x(-65 + x) = 1
5x + 8888 + (-65 * x + x * x) = 1
5x + 8888 + (-65x + x2) = 1

Reorder the terms:
8888 + 5x + -65x + x2 = 1

Combine like terms: 5x + -65x = -60x
8888 + -60x + x2 = 1

Solving
8888 + -60x + x2 = 1

Solving for variable 'x'.

Reorder the terms:
8888 + -1 + -60x + x2 = 1 + -1

Combine like terms: 8888 + -1 = 8887
8887 + -60x + x2 = 1 + -1

Combine like terms: 1 + -1 = 0
8887 + -60x + x2 = 0

Begin completing the square.

Move the constant term to the right:

Add '-8887' to each side of the equation.
8887 + -60x + -8887 + x2 = 0 + -8887

Reorder the terms:
8887 + -8887 + -60x + x2 = 0 + -8887

Combine like terms: 8887 + -8887 = 0
0 + -60x + x2 = 0 + -8887
-60x + x2 = 0 + -8887

Combine like terms: 0 + -8887 = -8887
-60x + x2 = -8887

The x term is -60x.  Take half its coefficient (-30).
Square it (900) and add it to both sides.

Add '900' to each side of the equation.
-60x + 900 + x2 = -8887 + 900

Reorder the terms:
900 + -60x + x2 = -8887 + 900

Combine like terms: -8887 + 900 = -7987
900 + -60x + x2 = -7987

Factor a perfect square on the left side:
(x + -30)(x + -30) = -7987

Can't calculate square root of the right side.

The solution to this equation could not be determined.

See similar equations:

| 25x^2=49x | | x+19=19+6 | | 5x-88+x*(x-65)=8888 | | 5x-88+x*(x-65)=8 | | 5x-88+x*(x-5)=8 | | x+14=17-19 | | 5/9(-37.8) | | x^2-4x+5=1 | | -14+2=x-1 | | (2x-1)=3 | | z+3/z-7=8/-3 | | -15=2x+3x | | .75=2x+9 | | 95-5x=22x+23 | | 2x+9=1.5 | | x-17=1-2 | | -55-9=9x+17 | | X^2-96x+256=0 | | x-11=9-10 | | d-6=7 | | x+6+x+9+x+3=x+1+x+1+x+4+x+4 | | 1.5b(3)=36 | | x/4+x/12=8 | | -8+4=x+6 | | -1/2x=23 | | y=17x^2+23x+19 | | -9-7=x-2 | | -5(-9z+13)=7(5z+19)-8 | | 9x-4=2x+78 | | 19g=-2(-4g-11) | | (1/16x^-8)^-1 | | -6(-9w-5)=-4(-12w-18) |

Equations solver categories